Peran Stakeholder dalam Pengembangan Desa Wisata Kerta Kecamatan Payangan Kabupaten Gianyar - Paristha, Ni Putu Tiya; Arida, I Nyoman Sukma; Bhaskara, Gde Indra (JURNAL MASTER PARIWISATA; Volume 08, Nomor 02, Januari 2022DO - 10.24843/JUMPA.2022.v08.i02.p13, 2022)
Tourism development will be optimal when the potential of an area can be managed properly by stakeholders, by maximizing coordination and integrating their roles and functions to manage their resources. The problems faced by Kerta Tourism Village indicate the weaknesses in its development, therefore efforts are required to improve potential management. One of them is by increasing the contributions through collaboration between stakeholders. This study aims to analyze the role of stakeholders and to formulate a collaborative model in the development of Kerta Tourism Village. The method utilized in this study is a qualitative method with data collection techniques through document analysis, observation, and in-depth interviews with stakeholders that involved in Kerta Village development. The results of this study showed the stakeholders have played their role, yet the involvement of businesses and the media are still relatively low. The collaborative model is formulated by placing the community as the core of development and supported by academics, government, business, and the media as the supporting actors. Keywords: Collaborative Model, Stakeholder, Tourism Village.